(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: This study aimed to describe the antibiotic resistance patterns of bacterial pathogens causing hospital-acquired pneumonia (HAP) in the intensive care unit (ICU) at Quang Ngai Provincial General Hospital. Method: An observational study was conducted using medical records of 68 HAP patients admitted to the ICU between January 2023 and April 2024. Data were collected on patient characteristics, microbiological test results, and bacterial antibiotic susceptibility. The susceptibility of bacterial strains to Beta-lactams, Aminoglycosides, Fluoroquinolones, and Glycopeptides was analyzed using SPSS 27.0. Results: The mean age of patients was 77.38 ± 13.37 years, with 52.9% aged ≥80. The average hospital stay was 28.76 ± 18.28 days. Among 64 microbiological specimens, sputum accounted for 89.1%, isolating 57 bacterial strains. The predominant pathogens were Acinetobacter baumannii (24.6%), Klebsiella pneumoniae (22.8%), and Escherichia coli (17.5%). Antibiotic susceptibility testing revealed that most pathogens exhibited high resistance to Beta-lactams. A. baumannii showed resistance to all Beta-lactams except imipenem/cilastatin (1/14 strains). E. coli demonstrated limited sensitivity to ceftazidime (3/10 strains) and meropenem (3/10 strains). K. pneumoniae and Pseudomonas aeruginosa retained moderate sensitivity to carbapenems, while Proteus mirabilis exhibited low sensitivity to imipenem/cilastatin and meropenem. Conclusion: The findings highlight the severe antibiotic resistance among HAP pathogens in the ICU, emphasizing the critical need for regular surveillance and updated antibiotic stewardship programs to optimize treatment and improve outcomes.